Laboratório de gestão à luz da teoria da aprendizagem experiencial e service learning : uma proposta para o curso de administração da Universidade Federal de Sergipe - Pedroso, Débora Tayane Rodrigues dos Santos (2022)
Management teaching in traditional ways has been criticized and considered not enough for the formation of Administrators who are good professionals, but also conscientious citizens. One of the main criticisms is the theory-practice dichotomy that results in poor preparation of future professionals. Seeking to bridge the gap between the contents covered in the classroom and the real context, new approaches are being disseminated, among them experiential learning and service learning (SL). Such methodologies focus on the active participation of the student in the teaching-learning process and their experiences. Furthermore, SL tries to incorporate in this training process, integration with the community through community services associated with academic content. That said, the general objective of this research is to propose the creation of a management laboratory with an experiential teaching methodology, more specifically service learning, for students of the Administration Course at the Federal University of Sergipe. For this, a qualitative research was carried out, supported mainly by the interpretivist paradigm, divided into two stages: exploratory and systematic. In the first one, an informal visit to the field was carried out, where the researcher talked to graduates in Administration and entrepreneurs, in addition to applying a questionnaire to Administration students at the Federal University of Sergipe. The second stage was divided into two phases and consisted of conducting a focus group with professors from the institution in addition to individual interviews. The data were analyzed using the content analysis technique and the findings of this research demonstrate that the present proposal has acceptability and can contribute positively to the interested public, that is, university, students and entrepreneurs.